CHRONIC EFFECT ANALYSIS OF MERCURY EXPOSURE ON COMMUNITIES AROUND ARTISANAL SMALL-SCALE GOLD MINING (ASGM) USING HUMAN BIOMONITORING (HBM) METHOD (CASE STUDY: WG, MR, DH, AND KB DISTRICT) - Mubiarto, Haryo
Artisanal Small-Scale Gold Mining (ASGM) activities have the potency to cause degradation of environmental quality (soil, water, air, and sediment) because tailing wastes containing mercury from the amalgamation process. In addition, mercury can also pose a health threat to human because it can perform biomagnification in the food chain process. Exposure to human over a long period of time can give a chronic effect on human. Therefore, the purpose of this study was to analyze mercury concentrations in water, rice, fish, and food crops were also evaluated to know their contribution to mercury concentrations in nails and hair through a Provisional Tolerable Weekly Intake (PTWI) analysis and analyze mercury concentrations in nails and hair as chronic exposure biomarkers. Besides, we also conducted Human Biomonitoring (HBM) analysis to assess mercury intoxication in the communities. Since miners in WG and KB District burn their amalgam in their home, it makes these two districts had more intoxicated respondents than other districts. The results showed that PTWI were significantly correlated with concentration mercury in nails both worker and non-worker also in both worker’s hair and non-worker’s hair. In multivariate regression, PTWI was the major predictor of mercury concentration in both worker’s nails and non worker’s nails also in both worker’s hair and non worker’s hair.